Reichswehr und Marine mit den Kokarden schwarz-weiss-rot nach einer neuen Verordnung des Reichspräsidenten (1933)
Reichswehr und Marine mit den Kokarden schwarz-weiss-rot nach einer neuen Verordnung des Reichspräsidenten.